Enhanced cooperation in an asymmetric model of tax competition - Hendrik Vrijburg; Ruud A. De Mooij (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper analyzes enhanced cooperation agreements in corporate taxation in a three country tax competition model where countries differ in size. We characterize equilibrium tax rates and the optimal tax responses due to the formation of an enhanced cooperation agreement. Conditions for strategic complementarity or strategic substitutability of tax rates are crucial for the welfare effects of enhanced cooperation. Simulations show that enhanced cooperation is unlikely to be feasible for small countries. When enhanced cooperation is feasible, it may hamper global harmonization. Only when countries are of similar size is global harmonization a feasible outcome.
Keywords: E62; F21; H25; H77; 330; tax coordination; asymmetry; enhanced cooperation agreements; strategic tax response; Unternehmensbesteuerung; Steuerharmonisierung; Steuerwettbewerb; Optimale Besteuerung; Mehr-Länder-Modell; Theorie